Microbial Community Dynamics and Biogeochemical Cycling in Microplastic-Contaminated Sediment - Xuanxuan Zhang; Dina Ding; Yinglin Liu; Zhiming Yao; Pingping Duan; Hanyu Yuan; Hanzhong Fan; Yanhui Dai (Nanomaterials, 2025)
Sediments are important repositories for microplastics (MPs) which exhibit higher microbial community richness and greater diversity than corresponding aqueous phases. Recently, the effects of MPs on microorganisms in sediments have received widespread attention. This review summarizes current knowledge on how MPs alter microbial diversity, composition, function, and biogeochemical cycling in sedimentary environments. The impacts of MPs on microorganisms in sediments can be affected by several factors, including MP type, the sedimentary environment, exposure time, and exposure concentration. Generally, biodegradable MPs cause more significant changes to the microbial community structure in sediments due to degradability and high bioavailability. Short-term exposure to MPs may enhance microbial diversity, and long-term exposure may lead to a reduction in diversity. High concentrations cause more serious impacts on microbial diversity than low concentrations. MPs mainly interfere with cycles of carbon, nitrogen, phosphorus, and sulfur in the sedimentary environment by changing microbial community structure, enzyme activity, and gene abundance. In conclusion, key research gaps are pinpointed, and future research directions presented. This review provides valuable insights into the health risks and ecological responses of MPs in sedimentary environments.